Investigating Students’ Writing Skills in Generating Descriptive Texts: Experiences Learned from English for Specific Purposes (ESP) Contexts in Privates Universities - Saori, Sopian; Sugianto, Sugianto; Christian Badilo, Kim (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2023)
Writing occupies a paramount role in the conveyance of ideas, demanding a profound comprehension of the nuances integral to crafting impeccable written compositions. The research under consideration was undertaken with the objective of delving into the writing skills of students and discerning the challenges they encounter in composing descriptive texts. Employing a mixed-method approach, the study engaged English learners at STIE AMM Mataram, constituting a cohort of 28 students. To attain a comprehensive understanding of their writing abilities and difficulties, the research employed writing tests and interviews as research instruments. The research outcomes revealed a mean score of 69.92 for the students, indicative of a concerning trend of inadequate proficiency in writing descriptive texts, essentially categorizing their abilities as 'poor.' A closer examination of the data delineated specific performance distributions among the students: 12% garnered scores below 60, designating them as 'poor,' while 40% fell within the 61-70 score range, also categorized as 'poor.' Moreover, 36% secured scores in the 71-80 range, positioning them in the 'average' category, and a mere 12% earned scores designated as 'very good. Vocabulary and organization stood out with ratings categorized as 'good to average,' showcasing relative strengths. Conversely, content, grammar, and mechanics were characterized by a 'fair to poor' categorization, underscoring significant areas of difficulty. In particular, students grappled with challenges concerning grammar, content development, and mechanical aspects of writing. In light of these findings, it is evident that students encounter multifaceted difficulties, particularly in the realms of grammar, content creation, and mechanics. As a viable solution, it is recommended that English teachers prioritize providing students with ample opportunities for writing practice. These opportunities should be designed to specifically enhance content development and grammar proficiency in writing descriptive texts.